La competencia de la comisión de eliminación de barreras burocráticas de indecopi en las sanciones administrativas de multas - Pacherres Conche, José Marvin (2014)
This thesis titled: "The Competition Commission Elimination of Bureaucratic Barriers INDECOPI in the Administrative Sanctions Fines" addresses the issue about the extent to which the Administrative Sanctions Fines will be competition for the Commission on Bureaucratic Barriers INDECOPI because under art. 10 of Legislative Decree No. 1014 by adding section 231-A No. 27444, the commission would be empowered to determine whether the administrative penalty may itself constitute an illegal or unreal barrier, however the same Commission Resolution No. 00035 - 2009 / CEB INDECOPI has denied having such jurisdiction, arguing that the Commission can assess the presence of illegal barriers to the failure that led to the punishment administered, this situation has now allowed state agencies as Municipalities impose heavy fines on companies investing in the country discouraging private investment. To analyze this problem has been studied through five chapters in our theoretical framework, considering that in the first chapter develops based on the Role of the State in the Freedom of Contract, In a second chapter pertains addressed to Bureaucratic Barriers a third chapter deals with the Fines in the Public Administration, and finally in the last two chapters the role of the Commission of the bureaucratic Barriers and municipalities in administrative penalties discussed. To formulate and contrast our hypothesis, ie, that Administrative Penalties Fines will be competition for the Commission on Bureaucratic Barriers INDECOPI the extent that they constitute illegal and irrational actions; has used the hermeneutic, deductive, inductive, synthetic methods, and analysis of the Resolutions of the Committee on Bureaucratic Barriers INDECOPI in recent years and the opinion of the doctrine getting itself to determine that the Administrative Sanctions Fines must be competition by the Commission of Bureaucratic Barriers accredited